Metals and Environment: Chemical Outputs From the Interaction Between Gilded Copper-Based Objects and Burial Soil - Graziani, Valerio; Iorio, Morena; Albini, Monica; Riccucci, Cristina; Di Carlo, Gabriella; Branchini, Paolo; Tortora, Luca (Frontiers in Materials, 2020)
Three-dimensional chemical mapping was adopted to investigate an ancient fire-gilded buckle found in Rome. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) were used to detect and locate degradation products aiming to identify the alteration processes. Inorganic and organic compounds present in the outermost part of such a class of cultural heritage objects can be considered the result of long-term interaction with the burial environment. ToF-SIMS depth profiling experiments can provide chemical information at the molecular level and high resolved spatial information (about 1 μm laterally, and 1 nm in depth). In this work, the attention was focused on the identification and localization of the ionic and molecular species involved in the degradation process. Results showed the presence of copper oxides, chlorides, and sulfides as common corrosion products but also the presence of species related to copper and bronze corrosion process such as atacamite and its polymorphs. 3D maps for all the relevant molecular species allowed to visualize at the same time the eruption of copper chlorides throughout the micro/nanochannels present on the gold surface, the recrystallization of compounds of minor elements from the substrate, a pathway followed by silico-aluminates from the surface towards the internal corrosion layers, but mostly the evidence of biological activity of Sulphur Reducing Bacteria (SRB) living in anaerobic conditions.